2001
DOI: 10.1074/jbc.m009088200
|View full text |Cite
|
Sign up to set email alerts
|

A Pancreatic β-Cell-specific Enhancer in the HumanPDX-1 Gene Is Regulated by Hepatocyte Nuclear Factor 3β (HNF-3β), HNF-1α, and SPs Transcription Factors

Abstract: The PDX-1 transcription factor plays a key role in pancreas development. Although expressed in all cells at the early stages, in the adult it is mainly restricted to the beta-cell. To characterize the regulatory elements and potential transcription factors necessary for human PDX-1 gene expression in beta-cells, we constructed a series of 5' and 3' deletion fragments of the 5'-flanking region of the gene, fused to the luciferase reporter gene. In this report, we identify by transient transfections in beta- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 45 publications
(46 reference statements)
3
67
0
Order By: Relevance
“…We have shown that rosiglitazone promotes elevated nuclear levels of FOXA2 over 24 h. FOXA2 is a known regulator of the Ipf1 gene promoter and plays a key role in Ipf1 gene expression both during pancreas development and in adult islets [19,20]. Nuclear/cytosolic localisation of FOXA2 in hepatocytes is regulated through Akt-mediated phosphorylation events [36].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have shown that rosiglitazone promotes elevated nuclear levels of FOXA2 over 24 h. FOXA2 is a known regulator of the Ipf1 gene promoter and plays a key role in Ipf1 gene expression both during pancreas development and in adult islets [19,20]. Nuclear/cytosolic localisation of FOXA2 in hepatocytes is regulated through Akt-mediated phosphorylation events [36].…”
Section: Discussionmentioning
confidence: 98%
“…Expression of the Ipf1 gene is also regulated in response to glucose [16]. The complex 4.5 kb Ipf1 gene promoter contains binding sites for many beta cell transcription factors, including hepatocyte nuclear factor 1α (HNF1α), IPF1 and FOXA2 [17][18][19][20]. FOXA2 is a member of the forkhead/winged helix family and has been identified as a key regulator of Ipf1 gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plasmid construct containing the human pdx-1 gene promoter linked to a luciferase reporter gene was kindly provided by Dr D. Melloul, Department of Endocrinology, Hadassah University Hospital, Jerusalem, Israel [44]. Transfected beta cells were exposed to cytokines and/or PIC for 24 h (same concentrations as above).…”
Section: Rt-pcr and Real Time Rt-pcrmentioning
confidence: 99%
“…Islet nuclear protein extraction and DNA-binding assays were performed as described in ref. 47. The NF-B binding mixture contained 30 mM Hepes, pH 7.9͞100 mM NaCl͞0.3 mM EDTA͞ 2.5 mM DTT͞1.5 mM MgCl 2 ͞2 g of poly (dI-dC)͞10% glycerol.…”
Section: Methodsmentioning
confidence: 99%